Design, Synthesis, and Biological Evaluation of Novel Peptide Gly3‐MC62 Analogues as Potential Antidiabetic Agents. (25th April 2015) - Yang, Baowei; Zhang, Chenyu; Li, Xue; Yan, Sijia; Wei, Wei; Wang, Xuekun; Deng, Xin; Huang, Wenlong; Qian, Hai
Abstract : Two series of conformationally constrained analogues fromGly 3 ‐ MC 62 were designed by scanning the residues Lys 1, Thr 2, Met 4, Lys 5, Met 7, and Ala 8 with an i‐(i + 2) lactam bridge consisting of a Glutamic acid–xaa–lysine (Glu–Xaa–Lys) scaffold and a diproline fragment. They were synthesized and evaluated for their antihyperglycemic effects. Through screening in normal and mice with diabetes mellitus, peptidesII ‐5, III ‐3, III ‐4, andIII ‐5 showed significant improvement in antihyperglycemic and antioxidative activities compared withGly 3 ‐ MC 62, especially the compoundIII ‐4 . The primary mechanism of the compounds (II ‐5, III ‐3, III ‐4, andIII ‐5 ) underlying this effect is the islet β ‐cells against oxidative damage induced by STZ, andIII ‐4 ‐treated mice showed considerable improvement in the preservation of beta cells in the pancreatic islets of DM mice. These data suggested thatIII ‐4 could be candidate for the future treatment of diabetes mellitus. Abstract : Two series of Gly 3 ‐MC62 analogues were synthesized and were evaluated for their antihyperglycemic effects. Antihyperglycemic effect ofIII‐4 was more potent than that of parent peptide Gly 3 ‐MC62.III‐4 merits further screening for antihyperglycemic/antioxidative effects.